Analisis High Order Thinking Skills (HOTS) Taksonomi Berpikir Kritis pada Permasalahan Fisika - Syaiful Rochman; Nirwana Nirwana (PendIPA Journal of Science Education, 2020)
The purpose of this research is to get the measurement result as a description of higher order thinking skill in taxonomy to critical thinking physics problem in SMA XI class. This study is descriptive qualitative through three stages, namely: initial development of the instrument, content validation and empirical, and measurement. The research has been conducted in the region of Central Bengkulu. The instrument used has been validated by the expert and applied rasch model. An empirical valiadation test was conducted by 95 students. A valid instrument is used to measure student's higher order thinking skills. The number of learners measured using a total sampling of 148 learners. The measurement result shows very high critical thinking 0,5%, ability critical thinking high 25%, ability medium critical thinking 55%, ability critical thinking low 19%, ability critical thinking very low 0, 5%. On the average it can be concluded that higher order thinking skills on taxonomy critical thinking students in Bengkulu Tengah included in medium criterion.